PENGARUH BOKASI LIMBAH SAYURAN TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH PADA TANAH ALUVIAL - JUWITA, JUWITA; SUSANA, RINI; ABDURRAHMAN, TATANG (Jurnal Sains Mahasiswa Pertanian, 2018)
THE EFFECTS OF VEGETABLES WASTE BOKASHION THE GROWTH AND YIELD OF ONIONON ALLUVIAL SOIL Juwita(1), Rini Susana(2), Tatang Abdurrahman(2).Agrotechnology programe study of agriculture facultyTanjungpura University Pontianak  ABSTRACT This study aims to determine the effect of vegetable waste bokashi on the growth and yield of the onion on alluvial soil. This research was conducted in experimental garden of Faculty of Agriculture, Tanjungpura University Pontianak for 2 months starting on April 4th to June 5th, 2017. This research used Randomized Complete Design which consists of 6 treatments and 4 replications, with each replication consists of 3 samples, and the total number is 72 plants. The treatment were a0= 0 g/polybag, a1= 160 g/polybag, a2= 320 g/polybag,            a3= 480 g/polybag, a4= 640 g/polybag, a5= 800 g/polybag. The variable observed in this study included the number of leaf per clump, height of the plant, this amount of tuber per clump, fresh weight of tuber per clump, and dry weight of tuber per clump. The result showed that the difference dose of vegetable waste bokashi gave significant effect to fresh weight of tuber per clump and dry weight per clump, but it gives not significant effect to number of the leaf per clump, height of the plant, number of tuber per clump. The result showed that application of the vegetable waste bokashi increase the fresh weight of the tuber per clump and dry weight of tuber per clump, and application of vegetable waste bokashi with 160 g/polybag dose is the effective dose for the growth and yield of the onion. Keywords: alluvial, onion, vegetable waste bokashi